2017
DOI: 10.1016/j.cellimm.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Burn injury influences the T cell homeostasis in a butyrate-acid sphingomyelinase dependent manner

Abstract: Following burn injury, a key factor for patients susceptible to opportunistic infections is immune suppression. Butyrate levels are important in maintaining a functional immune system and these levels can be altered after injury. The acid sphingomyelinase (Asm) lipid signaling system has been implicated in a T cell actions with some evidence of being influenced by butyrate. Here, we hypothesized that burn-injury changes in butyrate levels would mediate Asm activity and, consequently, T cell homeostasis. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Butyrate is well known for regulating T-cell function and the systemic immune response [ 31 ]. We have previously shown that colonic butyrate levels decrease following burn injury [ 26 ] and that butyrate reduces T cell death in an acid sphingomyelinase-dependent manner [ 32 ]. T cell depletion is a key component in burn-induced immunosuppression and enhanced susceptibility to opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate is well known for regulating T-cell function and the systemic immune response [ 31 ]. We have previously shown that colonic butyrate levels decrease following burn injury [ 26 ] and that butyrate reduces T cell death in an acid sphingomyelinase-dependent manner [ 32 ]. T cell depletion is a key component in burn-induced immunosuppression and enhanced susceptibility to opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…The following cell types were identified using the following antibody combinations: Neutrophils: Ly-6G and CD11b; Resident macrophages: F4/80 and CD11b; Total CD4 T cells: CD4 and TCRβ (naïve: CD62L high ); Total CD8 T cells: CD8 and TCRβ (naïve: CD62L high ); and immature macrophages: Ly-6G − , Ly-6C + , and CD31 low . Cells were analyzed using an Attune Acoustic Focusing Cytometer and accompanying software (Life Technologies, Carlsbad, CA, USA), as previously described [ 38 ]. The BAL IL-6 and G-CSF levels were determined by a cytometric bead array per the manufacturer’s instructions (BD Biosciences) and as previously described [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients with extensive burns have burn-related immunosuppression [7, 8]. However, reports on the reactivation of latent VZV manifesting as either shingles or disseminated zoster in burn patients are rare.…”
Section: Discussionmentioning
confidence: 99%